Sick of your colleagues' absence? - Patrik Hesselius; Per Johansson; Peter Nilsson (Institute for Labour Market Policy Evaluation (IFAU), 2009)
We utilize a large-scale randomized social experiment to identify how coworkers affect each other's effort as measured by work absence. The experiment altered the work absence incentives for half of all employees living in Göteborg, Sweden. Using administrative data we are able to recover the treatment status of all workers in more than 3,000 workplaces. We first document that employees in workplaces with a high proportion treated co-workers increase their own absence levels significantly. We then examine the heterogeneity of the treatment effect in order to explore what mechanisms are underlying the peer effect. While a strong effect of having a high proportion of treated coworkers is found for the nontreated workers, no significant effects are found for the treated workers. These results suggest that pure altruistic social preferences can be ruled out as the main motivator for the behaviour of a nonnegligible proportion of the employees in our sample.
Keywords: C23; C93; J24; 330; Social interactions; employer emkloyee data; work absence; fairness; reciprocal preferences; Fehlzeit; Dauer; Soziale Norm; Krankheit; Test; Schweden